Post-Receptor Inhibitors of the GHR-JAK2-STAT Pathway in the Growth Hormone Signal Transduction - Wójcik, Maciej (Int J Mol Sci, 2018)
The growth hormone (GH) plays a key role in the regulation of metabolic processes in an organism. Determination of the correct structure and functioning of the growth hormone receptor (GHR) allowed for a more detailed research of its post-receptor regulators, which substantially influences its signal transduction. This review is focused on the description of the post-receptor inhibitors of the GHR-JAK2-STAT pathway, which is one of the most important pathways in the transduction of the somatotropic axis signal. The aim of this review is the short characterization of the main post-receptor inhibitors, such as: cytokine-inducible SH2-containing protein (CIS), Suppressors of Cytokine Signaling (SOCS) 1, 2 and 3, sirtuin 1 (SIRT1), protein inhibitors of activated STAT (PIAS) 1, 3 and PIAS4, protein tyrosine phosphatases (PTP) 1B and H1, Src homology 2 (SH2) domain containing protein tyrosine phosphatase (SHP) 1, 2 and signal regulatory protein (SIRP) α1. The equilibrium between these regulators activity and inhibition is of special concern because, as many studies showed, even slight imbalance may disrupt the GH activity causing serious diseases. The regulation of the described inhibitors expression and activity may be a point of interest for pharmaceutical industry.